Sámi Traditional Reindeer Herding Knowledge Throughout a Year: Herding Periods on Snow-Covered Ground - Eira, Inger Marie Gaup; Turi, Ellen Inga; Turi, Johan Mathis (Springer International Publishing, 2022)
Abstract Sámi traditional reindeer herding knowledge is the basis decisions in time and space made by Sámi reindeer herders with emphasis on periods and cycles and related to reindeer husbandry on snow-covered land. This chapter outlines aspects of the Sámi traditional knowledge used by reindeer herders in Western Finnmark performing reindeer herding during periods with snow on the ground. We will highlight the periods from October till April, as these constitute the critical bottlenecks in the annual herding cycle. Using methods for communicating with herders and co-production of knowledge between reindeer herders and science, this chapter outlines traditional reindeer herding periods and cycles through the year focusing particularly on aspects of herding on snow-covered ground. Reindeer herding strategies and practices are highly complicated and systematic enterprises containing different types of knowledge on how the biological and gender-based behavioral aspects of reindeer and the movement of the reindeer in time and space are connected to climate, temperature, and snow metamorphism. This includes knowledge about the different seasons, cycles, and periods in a reindeer year. Reindeer herding periods and cycles contain different sub-cycles that are a part of a larger system based on the year, the lunar month and day/night, e.g., cycles related to the use of areas throughout the year; the biological cycles of reindeer, like rutting season, calving season, dropped or cast antlers and moulting fur; sexual behavioral cycles; cycles relative to climate and snow, the cycles of sexual maturity, cycles of extreme years and cycles that include reindeer herding periods throughout the year.